Associations Between Academic Motivation, Academic Stress, and Mobile Phone Addiction: Mediating Roles of Wisdom. - Yaghoobi, Abolghasem; Karimi, Kambiz; Asoudeh, Maryam; Mohammadi, Sahar (International Journal of Mental Health & Addiction, 2025)
This research aimed to examine the impact of academic motivation and academic stress on mobile phone addiction, with a focus on the mediating role of wisdom. Employing a descriptive-correlational approach within an applied research framework, the study surveyed 375 female high school students from two institutions in Hamedan district using convenience sampling. Utilizing instruments including Ardelt's wisdom questionnaire (2003), Gadzella's academic stress questionnaire (1991), Koo Hy's phone addiction scale (2009), and Harter's academic motivation questionnaire (1981), data were analyzed through structural equation modeling. The results revealed that wisdom significantly mediated the relationships between academic stress, motivation, and mobile phone addiction. Notably, the direct effects of stress on wisdom and mobile phone addiction were statistically significant, as were the indirect effects of stress and motivation on mobile phone addiction. While the direct effect of motivation on mobile phone addiction was not significant, wisdom demonstrated a substantial direct influence on mobile phone addiction. This investigation sheds light on the intricate dynamics of these variables and underscores the vital role of wisdom in understanding and addressing mobile phone addiction.